A DECISION SUPPORT SYSTEM BASED ON OPTIMIZATION METHODS FOR OPTIMIZING DUHOK UNIVERSITY TRAFFIC PROBLEM - SALEH, SAGVAN ALI; MOHAMMAD, SERWAN ALI; SARHAN, RAFID SALIH; KAMAL, RAWAN RASHAD; AHMED, HUDA MAWLOUD; YOUNIS, AHLAM YOUSIF; MIRZA, KAHRAMAN KHODEDA (Journal of Duhok University, 2023)
Combinatorial optimization problems have previously proven to be significant and appealing for both basic research and practical applications. In this work, a real-life problem at Duhok University is considered, named as Duhok University Traffic Problem. Traffic bottlenecks, difficulties in moving, transportation cost in terms of time and financial and other problems in Duhok University are addressed as a series problems. In this paper a decision support system based on optimization methods are proposed in order to optimize a public transportation network to reduce the impact of the considered problem. The authors are first simulated the problem as a well-known optimization problem named as travelling salesman problem. Second, the problem is represented mathematically by introducing a mathematical programming model. Third and last, a decision support system based on three optimization methods are proposed in order to help in solving the considered problem, which are: greedy method, local search method, and artificial bee colony method. Computational results showed that, all the three proposed algorithms optimized and enhanced the transportation network in Duhok University, where Artificial Bee Colony presented high quality improvement by 36.48% and outperformed both, the greedy algorithm (13.81%) and the local search algorithms (31.45%).